The genus Diplommatina Benson, 1849 (Gastropoda: Caenogastropoda: Diplommatinidae) in Nepal, with the description of seven new species - Budha, Prem B.; Naggs, Fred; Backeljau, Thierry (European Journal of Taxonomy, 2017)
This paper deals with the taxonomy and faunistics of the genus Diplommatina in Nepal. Altogether 16 species are reported, seven of which are new to science viz. D. abiesiana sp. nov., D. fistulata sp. nov., D. godawariensis sp. nov., D. maipokhariensis sp. nov., D. salgharica sp. nov., D. shivapuriensis sp. nov. and D. syabrubesiensis sp. nov. Information on nine previously reported species is provided: D. exserta Godwin-Austen, 1886, D. folliculus (L. Pfeiffer, 1846), D. miriensis Godwin-Austen, 1917, D. munipurensis Godwin-Austen, 1892, D. oviformis Fulton, 1901, D. pachycheilus Benson, 1857, D. regularis Fulton, 1901, D. silvicola Godwin-Austen, 1886 and D. sperata W.T. Blanford, 1862. Although D. canarica was once reported from Nepal, it is not treated here as it is an endemic of the Western Ghats. A dichotomous identification key for all Nepalese species is presented.